Features of the Structure of the Regulation of the Verkhovna Rada of Ukraine: Some Theoretical and Legal Aspects - Linetskyi S. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Рurpose. The purpose of the research is to analyze the current state and the main regularities of the construction of the structure of the Regulation of the Verkhovna Rada of Ukraine (Regulation) as a special legislative act, to clarify the conditioning of this structure by special legal factors, as well as to formulate the foundations of a scientific approach to determining the optimal structure of this legislative act. Method. The methodology includes a comprehensive analysis and generalization of available scientific and theoretical material and the formulation of scientific and legal conclusions and recommendations. During the study, the following research methods were used: dialectical, analytical-synthetic, hermeneutic, systemic-structural, prognostic. The results. In the process of research, it was found that the structure of the Regulation is determined by its legal nature and the functions and powers of the Verkhovna Rada of Ukraine. optimal legal impact of the Regulation on the regulation of parliamentary procedures and some other related legal relations, referred to the subject of regulation of this legislative act. It is proved that the structure of the Regulation is an objective legal phenomenon determined by the processes of formation and development of parliamentarism in Ukraine, its constitutionalization and legislative institutionalization, stabilization of parliamentary procedures based on the constitutional certainty of the functions and powers of the Verkhovna Rada of Ukraine. It is shown that the determining special-legal (normative) factor in the structuring of the Regulation was the Constitution of Ukraine, which has not yet exhausted its potential in this sense. It is substantiated that the further structuring of the Regulation is related to the resolution of the dichotomy in the regulatory plane, where the trend of strengthening the casuistic nature of regulatory procedures is opposed by the trend of simplifying their legal regulation. These two trends are objectively acting diametrically as directions of development of the structure of the Regulation. The optimal path is a rational and balanced combination of both approaches, ensuring the dominance of the constitutionality of all procedures at all stages of their implementation in the parliament. Originality. In the research process, it was established that the modernization of the content of the Regulation should take place on the basis of scientific ideas about the optimality of its structural construction. The basis of the concept of the structural construction of the Regulation should be the requirements of ensuring its constitutionality, logic and consistency of the presentation of normative material, continuity, compliance with current regulatory requirements for the structures of legislative acts, taking into account the need for full and continuous regulation of parliamentary procedures, the impracticality of structural expansion of the Regulation due to additional inclusion in of normative material unrelated to the regulation of parliamentary procedures. Practical significance. The results of the research can be used both during the current (preparation of current changes to the Regulation) and during prospective (planning of complex changes to the Regulation) legislative work on improving the structure and content of the Regulation, as well as during further scientific research of the sources of parliamentary law of Ukraine, their features and legal nature.